Natural oral care in dental therapy - Chauhan, Durgesh Nandini; Singh, Prabhu Raj; Shah, Kamal; Chauhan, Nagendra Singh (John Wiley & Sons, Inc. ; Scrivener, 2020)
"Patients increasingly seek integrated and anticipatory approaches to their healthcare. In this altering health environment, oral healthcare specialists can influence and expand their long-standing commitment to the preventative care model. Nowadays oral care specialists need to increasingly focus on the interdisciplinary connections between oral health, heart health, gastrointestinal health, etc. This important new volume will be valuable to Principal Dentists, Oral Hygienists, pharmacognosy expert, Natural product formulation scientist alike, either as a textbook or as a reference. It is a must-have for any dentist library and Herbal industry. Discusses natural products that can be used to treat oral diseases and their scientific basis for how these natural product act. Natural products for oral health care are on the increase worldwide and this is the first book to cover all the herbal antibiotics. The 26 chapters in this unique book explore all the measures to utilize the natural oral care obtained from plants, animals and mineral drugs for dental care"--